CrN precipitation and elemental segregation during the decay of expanded austenite. (6th June 2016) - Manova, D; Lotnyk, A; Mändl, S; Neumann, H; Rauschenbach, B
Abstract: Nitrogen insertion into austenitic stainless steel at elevated temperatures leads to anomalous fast nitrogen diffusion and the formation of an expanded fcc phase which is known as expanded austenite. In situ x-ray diffraction measurements during low energy nitrogen ion implantation into steel AISI 304 at 475 °C and short annealing at 575 °C were performed in conjunction with transmission electron microscopy investigations. They show the time dependent decay of this expanded phase with coalescing and growing CrN precipitates. There is elemental segregation associated with this decay where Fe is absent very early from the Cr–N containing precipitates. Ni is segregating towards the Fe-rich matrix more slowly. At the same time, the microstructure—decayed phase vs expanded austenite—is visible in SIMS cluster analysis.